2021
DOI: 10.3390/catal11080920
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of Cycloalkyl-Fused Aryliminopyridyl Nickel Complexes toward Ethylene Polymerization by QSPR Modeling

Abstract: Quantitative structure–property relationship (QSPR) modeling is performed to investigate the role of cycloalkyl-fused rings on the catalytic performance of 46 aryliminopyridyl nickel precatalysts. The catalytic activities for nickel complexes in ethylene polymerization are well-predicted by the obtained 2D-QSPR model, exploring the main contribution from the charge distribution of negatively charged atoms. Comparatively, 3D-QSPR models show better predictive and validation capabilities than that of 2D-QSPR for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The findings showed that the bulky phenyl ring substituents and the net charges on the core metal and N atoms were favorable for the catalytic activity [19]. Subsequently, 2D-and 3D-QSPR were employed to examine the different catalytic performances of cycloalkyl-fused aryliminopyridyl nickel complexes, and the 3D contour maps depicted that smaller sizes of cycloalkyl-fused rings favored catalytic activity while hindering an increase in molecular weight [20].…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the bulky phenyl ring substituents and the net charges on the core metal and N atoms were favorable for the catalytic activity [19]. Subsequently, 2D-and 3D-QSPR were employed to examine the different catalytic performances of cycloalkyl-fused aryliminopyridyl nickel complexes, and the 3D contour maps depicted that smaller sizes of cycloalkyl-fused rings favored catalytic activity while hindering an increase in molecular weight [20].…”
Section: Introductionmentioning
confidence: 99%